1955
DOI: 10.1677/joe.0.0120050
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Growth Hormone and the Glucose Utilization of Rat Diaphragm

Abstract: Growth hormone has been reported to cause either a depression or a stimulation of the glucose uptake of isolated rat diaphragm. The present paper describes further work on the two effects.1. Anaerobic conditions during the preparation of the diaphragm for incubation affect the glucose uptake and alter the response of the muscle to growth hormone. By controlling the oxygen tension in the diaphragm immediately after excision, variation of the glucose uptake and the effect of the hormone is reduced.2. Solutions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1957
1957
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…This is important since the nature of the dose-response curve of B 168 would be much easier to explain if factor (1) were considered as a mixture of two agents. Ottaway & Bulbrook (1955) have suggested that a single type of cell could show a biphasic response to a single hormone, but demonstration of such an effect calls for a demonstrably single hormone. At present it is not possible to determine whether the growth hormone itself has depressant, stimulant, biphasic or zero effect on the glucose uptake of the heart.…”
Section: Sylvia Bronk and R B Fisher Discussionmentioning
confidence: 99%
“…This is important since the nature of the dose-response curve of B 168 would be much easier to explain if factor (1) were considered as a mixture of two agents. Ottaway & Bulbrook (1955) have suggested that a single type of cell could show a biphasic response to a single hormone, but demonstration of such an effect calls for a demonstrably single hormone. At present it is not possible to determine whether the growth hormone itself has depressant, stimulant, biphasic or zero effect on the glucose uptake of the heart.…”
Section: Sylvia Bronk and R B Fisher Discussionmentioning
confidence: 99%
“…The presence of insulin-like activity in growthhormone preparations has been reported (Park, Brown, Comblath, Daughaday & Krahl, 1952;Ottaway & Bulbrook, 1955), and partial separation of the activity from growth-hormone preparations, using ultrafiltration, was reported by Ottaway & Paul (1957). Separation and complete purification of a peptide with insulin-like properties has now been accomplished by electrophoretic techniques.…”
Section: Proceedings Of the Biochemical Society 21pmentioning
confidence: 99%
“…Since Ottaway (1953) had suggested that the insulin-like effects of growth hormone might be due to displacement of insulin from inactive tissue loci, Manchester and Young repeated the test with growth hormone in the presence of quantities of insulin antiserum which blocked the effects of small quantities of insulin; the growth hormone stimulation was unimpaired, implying that it was not due to contamination w 7 ith, or displacement of, insulin. found beef growth hormone (50 ^g./ml. )…”
Section: Growth Hormonementioning
confidence: 99%
“…This raises the possibility that the humoral inhibitor is a fragment of growth hor mone carried with the ß-lipoprotein of rat serum, and possibly with other serum proteins of other species ( Vallance-Owen et al, 1958 ). Other aspects of the interrelationship between the action of insulin, growth hor mone, and/or cortical steroids upon isolated rat diaphragms have been dealt with by Verzar and Wenner (1948), Bartlett et al (1949), Ottaway (1953Ottaway and Bulbrook, 1955), and in the reviews by Ketterer et al (1957), and Manchester and Young (1961). Stadie (1954) found that the anti-insulin effect of injected pituitary factors upon glycogen synthesis was not due to a reduction of the quantity of in sulin which became attached to the diaphragm, but to interference with the effect of that which did become attached.…”
Section: Rat Diaphragmmentioning
confidence: 99%